Lack of association between single nucleotide polymorphisms in TCF7L2 and T2DM in the Chinese Yao population: A case-control study. Issue 12 (26th March 2021) - Sun, Shi-Yu; Huang, Run-Ze; Huang, Huang; Zhang, Ming-Qi; Sun, Hui-Lin
Abstract : Abstract: Single-nucleotide polymorphisms (SNPs) in the transcription factor 7-like 2 (TCF7L2) gene have been identified to be associated with the susceptibility to type 2 diabetes mellitus (T2DM) in various populations worldwide, but the results in Chinese are conflicting, and no data are available about the Liannan Yao population. Therefore, this study aimed to investigate the association of the TCF7L2 gene polymorphisms (rs12255372, rs7903146, rs7901695, rs11196205, and rs7895340) with T2DM in the Yao population living in the rural areas in the Liannan Yao Autonomous County. This was a case-control study of 28 subjects with T2DM or prediabetes and 52 non-T2DM controls, all from the Chinese Yao population and recruited between January 2019 and June 2020. Patients with T2DM and prediabetes were grouped as the case group. The five SNPs (rs12255372, rs7903146, rs7901695, rs11196205, and rs7895340) were examined by polymerase chain reaction and direct genomic DNA sequencing in case and control groups. The subjects in case group were older than the controls (55±14 vs 48 ± 15 years, P  = .047), had higher FBG levels (9.31 ± 5.43 vs 4.09 ± 0.81, P  < .001), higher TC (5.79 ± 1.29 vs 5.13 ± 1.18 mmol/L, P  = .025), and higher triglycerides (2.94 ± 2.04 vs 1.86 ± 1.39 mmol/L, P  = .003). The genotypic distribution for each of the SNPs was in agreement with the Hardy-Weinberg equilibrium. There were no statistically significant differences in the distributions of genotypes or alleles at all five SNPs of the TCF7L2 gene between the case and control groups (all P  > .05). TCF7L2 SNPs were not associated with T2DM in the Liannan Yao population.